Clinical outcomes with ABO antibody titer variability in a multicenter study of ABO‐incompatible kidney transplantation in the United Kingdom. Issue 11 (26th August 2016) - Bentall, Andrew; R. Barnett, A. Nicholas; Braitch, Manjit; Kessaris, Nicos; McKane, Will; Newstead, Chas; McHaffie, Gavin; Brown, Alison; Griffin, Sian; Mamode, Nizam; Briggs, David; Ball, Simon
Abstract : BACKGROUND: ABO blood group‐incompatible kidney transplantation (ABOiKTx) outcomes are good, but complications are more common than in conventional transplantation. Regimens that use extracorporeal antibody removal therapy (EART) and enhanced immunosuppression are guided by titration of ABO blood group antibodies (using hemagglutination [HA] dilution assays), and these assays vary significantly in performance between centers. This study aims to describe the differences in titer measurement and the effect on clinical practice and outcomes. STUDY DESIGN AND METHODS: This multicentre, prospective cohort study of 100 ABOiKTx recipients assessed treatment and outcome data, including HA assay results measured retrospectively in a single central laboratory. RESULTS: Patient and allograft survival at 1 year was 99% and 94%, respectively. There were significant differences in the number of pretransplantation EART sessions in centers undertaking plasma exchange (PEx), compared with immunoadsorption (IA) (median, 6 vs. 4 sessions; p = 0.007). The pre‐EART HA titer in both groups was the same when centrally assayed. The local HA assay used to guide treatment yielded significantly higher titers in centers undertaking PEx compared with IA (median, 128 vs. 32; p < 0.005). Patients undergoing PEx rather than IA were significantly more likely to suffer postoperative hematoma (12.9% vs. 1.8%; p = 0.05) or any perioperative collection requiring drainage (19.4% vs. 3.6%; p = 0.02). CONCLUSION: The colinearity of HA assay sensitivity with the receipt of PEx and EART limits some conclusions regarding the likely direction of causation. However, the association of differences in clinical practice with recognized perioperative complications of ABOiKTx identifies targets for further investigation and quality improvement.